Avaliação do Programa Busca Ativa e seu impacto no monitoramento da frequência escolar na rede municipal de ensino de Fortaleza-Ceará - Capelo, Carolina Sonntag (2025)
This research deals with the Active Search Program as a public policy implemented in the municipal public school system of Fortaleza, Ceará. The research aims to evaluate the contributions of the Active Search Program to the retention of students in the initial years of Elementary School, based on the actions developed in a public school in the city of Fortaleza, from the perspective of the school management and the monitors who work in this policy. With this, it seeks a greater understanding of the implementation process and the effects of the program in the municipal public schools of Fortaleza. The investigation adopts a qualitative approach, using fieldwork and document analysis. The research raises contributions to the understanding of the dynamics and challenges of identifying children and adolescents who are out of school or who have attendance problems and promoting an environment where all children and adolescents can have access and continue their school trajectory. This research also considers the continuities, changes and transformations of municipal educational policies, as well as using data from schools and the Municipal Department of Education (SME) to identify students who are not attending school regularly or who are out of the school system. The evaluative perspective adopted for the analysis of the policy is based on the assumptions of In-Depth Evaluation. The methodological approach adopted involves the collection of empirical data through semi-structured interviews with the school community: principals, coordinators, teachers and monitors, in addition to the analysis of the program's guiding and structuring documents. The research revealed that active search improves school attendance, especially among students in vulnerable situations. The main challenges are the resistance of some families, insecurity during visits and the lack of training of agents. The most effective strategies involve phone calls, home visits and dialogue with those responsible. The participants emphasize the need for more support, training and appreciation of professionals. Academically, the relevance of this study is the possibility of providing a comprehensive analysis of a local program in the context of educational policies. Therefore, the implications of the results for the active search policy in Fortaleza are clear and indicate that the policy has fulfilled its role efficiently in combating school dropout and promoting educational inclusion. Despite the positive results, the analysis suggests that some improvements can be made to further expand the impact of the policy, especially in relation to the coverage and depth of the actions implemented